Russian rap and its literary value: analysis of social-political themes in the texts of Miron Fedorov (Oxxxymiron) - Kucherova, Angelina (Vilnius University Open Series, 2024)
This article presents an analysis of the literary value of Russian rap through the lens of Miron Fedorov, better known as Oxxxymiron. The focus of the research lies in the social-political themes expressed in his lyrics. The article explores how rap texts serve as a means of profound literary expression, enabling the author to provide their responses to pressing societal issues. This study contributes to the understanding of how rap music can function as a form of literature and how it fosters a dialogue on crucial topics within contemporary society.